Practices of Peasant Literacy in the Short Stories by Žemaitė - Bleizgienė, Ramunė (Tautosakos darbai, 2019)
This article focuses on various literacy-related activities of the Lithuanian peasants from the end of the 19th – beginning of the 20th century, as described in the short stories by the renowned female Lithuanian writer and educator Julija Žymantienė (1845–1921) writing under a pen name Žemaitė. According to the recent research on literacy, such activities can be perceived as social practices depending on specific social and cultural context. Lithuanian research works addressing the issues of peasant literacy at the turn of the 19th – 20th centuries typically deal with cases of higher, i.e. functional literacy. Short stories by Žemaitė present a unique opportunity to look at the Lithuanian peasants still on the verge of entering the world of the secular literature. These stories often describe illiterate country people encountering the written word only at the collective reading events, when a somewhat more educated person would read aloud to a group of listeners, explaining more complicated fragments of the text to them. Such scenes of collective reading are rather frequent particularly in the early stories by Žemaitė, indicating that such peasant pastime growing increasingly popular from the end of the 19th century could be regarded as one of the most important ways of spreading the secular written word in the Lithuanian countryside. However, Žemaitė also presents evidence that even this facilitated mode of literacy imitating forms of verbal communication had hard time competing with the more traditional ways of communication favored by the village people (such as conversations, singing, playing cards, etc.). In her short stories, Žemaitė records numerous other realities from the turn of the centuries elucidating the ways by which written word entered the Lithuanian villages and the reactions it encountered from the new peasant readership, as well as changes that spread of literacy inspired in the traditional village communities of the time. Short stories by Žemaitė support the assumption made by historians maintaining that smuggling and spread of the illegal Lithuanian publications was mostly pursued by smallholders and poor peasants or craftsmen. The wealthy farmers as a rule regarded this innovation rather skeptically. The short stories present two opposing attitudes towards spreading of the illegal publications in the countryside and towards reading in general. One of such attitudes could be labelled as traditional, another one as modern. Supporters of the traditional view are scarcely individualized in the short stories; their voices being heard only in the group conversations. They are rather opposed to the publishers and promoters of the Lithuanian secular publications, as well as to the publications themselves. Characters supporting more modern views actively read and promote the illegal Lithuanian publications, being well aware of their importance and value. It should be noted that women are often depicted as more open-minded and enthusiastic about the new developments. Although the social and cultural situation at the turn of the 19th – 20th centuries was significantly less favorable for women seeking to achieve higher levels of literacy, Žemaitė testifies to the changes already taking place: namely, women gradually become active and independent readers rather than just passive listeners. True, all the writers and independent readers capable of reflecting upon the role of writing both in their personal life and in that of the community, are still exclusively men. Žemaitė herself viewed the spread of literacy in the Lithuanian countryside most positively. Her attitude was revealed already in her first short story entitled “Matchmaking”, and it never changed. Characters in her subsequent stories that are more educated and fonder of reading newspapers and books are depicted as dreaming of the better future for the whole society, which could be allegedly achieved by abolishing the restrictions imposed on the free press and by introduction of the mass literacy. These characters usually assert positive value of the Lithuanian books and periodicals, and are actively engaged in reading and promoting them, thus standing in stark opposition to the negative characters that have attended the Russian schools imposed by the tsarist government and generally disregard the Lithuanian writing. This opposition should be regarded as means of supporting the Lithuanian publications and promoting them among the peasants – the means that the author keenly employed.